Estimation of Aboveground Carbon Stock in The Pertamina Hulu Rokan (PHR) Forest in Pinggir District, Bengkalis Regency, Riau Province - Pebriandi, Pebriandi; Yoza, Defri; Sukmantoro, Wishnu; Sribudiani, Evi; Darlis, Viny Volcherina; Somadona, Sonia; Rangkuti, Ahmad Baiquni (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2023)
Extreme climate change affects human life. One of the causes of climate change is the increase of CO2 gas in the air. Forests can absorb CO2 from the air and store it in the form of tree biomass through the process of photosynthesis. One of the forests that can absorb and store carbon is Pertamina Hulu Rokan (PHR) forest, therefore it is necessary to conduct research on estimating the carbon content of PHR Forest area. The methods to be used in this research are non-destructive sampling and destructive sampling methods. The method with harvesting is only for seedlings, undergrowth and litter, while for saplings, poles, trees and necromass with the method without harvesting. Aboveground carbon storage in PHR forest was found to be 95.37 tonnes/ha. The largest carbon stocks were from trees (68.96 tonnes/ha), poles (13.06 tonnes/ha), necromas (5.70 tonnes/ha), litter (3.72 tonnes/ha), saplings (3.54 tonnes/ha) and the smallest carbon stocks were seedlings and understorey (0.39 tonnes/ha).